Analisis Perbandingan Sistem Pendukung Keputusan Metode SAW dengan Metode TOPSIS Berbasis Website untuk Penerimaan Beasiswa di Yayasan Aldiana Nusantara - Devan Rizaldi (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2024)
Information systems now play a crucial role in various fields, including education. Yayasan Aldiana Nusantara (YAN), which supports students from low-income backgrounds, faces challenges in selecting scholarship recipients. To streamline this process, this research designs a web-based Decision Support System (DSS) using the Simple Additive Weighting (SAW) and Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) methods. The system considers criteria such as class, KPS/KIP/KKS recipients, parents' income, report card grades, and extracurricular activities. The DSS is developed using the Waterfall model, PHP, and MySQL, with four types of access rights: Administrator, Judge, Student, and Foundation Leader. Sensitivity testing shows that the SAW method is more responsive to changes in criteria compared to TOPSIS, with a sensitivity value of 2.98 for SAW and 0.022 for TOPSIS. These results indicate that SAW is more optimal in assisting YAN in effectively and efficiently selecting scholarship recipients.